Research on Gearbox Fault Diagnosis Based on LMD Energy Entropy - Xu Le; Li Wei; Zhang Bo; Zhu Yubin; Lang Chaonan (Jixie chuandong)
Aiming at the problem that it is difficult to identify the composite fault characteristics of gearboxes in the case of small samples, a local mean decomposition(LMD) gearbox fault diagnosis method based on energy entropy is proposed. The LMD method is used to process the gearbox vibration signal to obtain several PF components；the dispersion value of component energy in the frequency domain is calculated using the uneven distribution of gearbox vibration signals in different states, which is the LMD energy entropy; the gearbox fault classification is carried out through the distribution of LMD energy entropy in different states. The experimental results show that in the case of small samples, the feature extraction and fault diagnosis of gearbox fault types can be accurately carried out based on the LMD energy entropy method, which also shows the superiority of this method in gearbox fault diagnosis.